Kunstminen : Neuerwerbungen zeitgenössischer Kunst : 1978-1990 - Peters, Hans Albert; von Wiese, Stephan; Adolphs, Volker; Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1990)
Adler, Jaroslav Iwan ; Albert, Hermann ; Alt, Otmar ; Alvermann, Hans Peter ; Antes, Horst ; Bardenheuer, Herbert ; Baumgarten, Bodo ; Bazile, Bernard ; Bendgens, Rolf ; Berke, Sybille ; Bernhard, Franz ; Beuys, Joseph ; Bielicky, Michael ; Blume, Anna ; Blume, Bernhard Johannes ; Body, Gabor ; etc.
Kunstminen : Neuerwerbungen zeitgenössischer Kunst : 1978-1990, Kunstmuseum Düsseldorf, 17.8. bis 21.10.1990
boek